2022
DOI: 10.18805/lr-4809
|View full text |Cite
|
Sign up to set email alerts
|

Management Strategies using Phytoextracts and Fungicides Against Cercospora Leaf Spot of Mungbean Incited by Cercospora canescens under in vitro and in vivo Conditions

Abstract: Background: Cercospora leaf spot of mungbean [Vigna radiata (L.)] caused by Cercospora canescens. It has become a severe menace to the growers of Rajasthan in India and in general causes economic losses under changing climatic scenario. Depending upon the temperature and humidity, it spreads rapidly in susceptible varieties causing premature defoliation and reduction in size of pods and grains. In this study management was taken through botanicals and fungicides is also an important segment in the present era,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Signi cant variation was recorded in morphological and cultural characteristics viz., colony texture, margins and colour, colour change in media, colony diameter, growth rate and spore characteristics in different isolates of P. maculans. Variations in cultural characteristics have also been observed in isolates of Cercospora kikuchii [27] Cercospora canesens [29], Cercospora beticola and P. paramaculans [30] and P. salmali [31,32] In order to discern the variability at molecular level, studies on pathogen were conducted for the rst time using ISSR markers. Out of 15 ISSR primers, ve polymorphic ISSR primers used in present study revealed a high level of polymorphism in different isolates of P. maculans in Kashmir, which indicated that these markers are suitable for studying the genetic diversity in mulberry leaf spot pathogen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Signi cant variation was recorded in morphological and cultural characteristics viz., colony texture, margins and colour, colour change in media, colony diameter, growth rate and spore characteristics in different isolates of P. maculans. Variations in cultural characteristics have also been observed in isolates of Cercospora kikuchii [27] Cercospora canesens [29], Cercospora beticola and P. paramaculans [30] and P. salmali [31,32] In order to discern the variability at molecular level, studies on pathogen were conducted for the rst time using ISSR markers. Out of 15 ISSR primers, ve polymorphic ISSR primers used in present study revealed a high level of polymorphism in different isolates of P. maculans in Kashmir, which indicated that these markers are suitable for studying the genetic diversity in mulberry leaf spot pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…Out of 15 ISSR primers, ve polymorphic ISSR primers used in present study revealed a high level of polymorphism in different isolates of P. maculans in Kashmir, which indicated that these markers are suitable for studying the genetic diversity in mulberry leaf spot pathogen. Various researchers have also reported ISSR markers suitable for studying the genetic diversity in different phytopathogenic fungi [29,33,34]. The Polymorphic Information Content (PIC) values varied from 0.219 to 0.395 in different ISSR primers with the highest value of 0.395 in primer number UBC-889 followed bu UBC-840 with PIC value of 0.350 indicating their suitability for studying the genetic variation in this pathogen.…”
Section: Discussionmentioning
confidence: 99%